Oxidative Stress in Hepatic Ischemia-Reperfusion Injury: The Role of Antioxidants and Iron Chelating Compounds - Galaris, D.; Barbouti, A.; Korantzopoulos, P. (Current Pharmaceutical Design, 2006)
Ischemia-reperfusion (IR) injury is a multifactorial process triggered when the liver or other organs are transiently subjected to reduced blood supply followed by reperfusion. It has been shown that
Keywords: Antioxidants